Physicochemical and microbiological analysis of common spices available in Bangladesh - Jubair, Abdullah; Hossain, Md. Murad; Zzaman, Wahidu; Sofia Murtini, Erni; Huda, Nurul (jurnal1, 2025)
This study aimed to assess nutritional composition, quality attributes and microbial load of different variety of turmeric (Curcuma longa), chili (Casicum annuum) and coriander (Coriandrum sativum) collected from different region of Bangladesh during April to October, 2023. Ash content in different spice ranged from 6.07% to 12.03% and protein ranged from 3.27% to 13.20%. Chili had the highest protein and coriander had the lowest. Chili contain more fat (17.21% to 20.21%) than turmeric (0.05% to 12.08%) and coriander (11.21% to 13.04%). In different varieties of chili capsaicin content, the American Trade Association (ASTA) color value and Scoville Heat Unit (SHU) values differed significantly between 0.08% to 0.32%, ASTA 58.1 to ASTA 74.25 and SHU 13000 to SHU 51000 respectively. In terms of analyzing curcumin content and color value of different varieties of turmeric, ranged from 1.98% to 3.02% and 33.26 to 50.74. In case of analyzing microbiological analysis of different spices, the total plate count (TPC) was found ranging from 3200 to 67000 where lowest TPC was found in turmeric (3200 to 8300). Salmonella spp. was detected in one sample of coriander. Nutritional composition, quality attributes and microbial load provide useful information for people who want to buy spices from other countries and for industrial use.